2014
DOI: 10.1080/13504509.2014.954023
|View full text |Cite
|
Sign up to set email alerts
|

Optimal infrastructure selection to boost regional sustainable economy

Abstract: The role of infrastructures in boosting the economic growth of the regions is widely recognized. In many cases, an infrastructure is selected by subjective reasons. Selection of the optimal infrastructure for sustainable economic development of a region should be based on objective and founded reasons, not only economical, but also environmental and social. In this paper is developed such selection through a hybrid method based on Delphi, analytical hierarchy process (AHP), and VIKOR (from Serbian, VIseKriteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…Results of this study indicated that noise pollution and air quality were the important criteria of environmental quality in Taipei. Vučijak, Kupusović, Midžić-Kurtagić andĆerić [3] evaluated sustainable hydropower by applying the VIKOR, Quijano H, Botero B and Domínguez B [4] used VIKOR for development of renewable sustainable energy plans, Martin-Utrillas, Juan-Garcia, Canto-Perello and Curiel-Esparza [6] integrated the VIKOR, fuzzy Delphi and AHP for selection of best infrastructure related to sustainable economy, Ren, Manzardo, Mazzi, Zuliani and Scipioni [8] combined the VIKOR and AHP for assessment of life cycle sustainability, Yazdani-Chamzini, Fouladgar, Zavadskas and Moini [7] used the VIKOR, SAW, ARAS, TOPSIS and MOORA for selection of the best renewable energy sources, Civic and Vucijak [9] utilized VIKOR for insulation options for warmth of buildings to increase energy efficiency, Kim and Chung [10] evaluated the vulnerability of the water supply to variability and climate change. In total, 13 past papers used the VIKOR technique in the fields of sustainability and renewable energy, which presented in Table 10.…”
Section: Sustainability and Renewable Energy Fieldsmentioning
confidence: 99%
“…Results of this study indicated that noise pollution and air quality were the important criteria of environmental quality in Taipei. Vučijak, Kupusović, Midžić-Kurtagić andĆerić [3] evaluated sustainable hydropower by applying the VIKOR, Quijano H, Botero B and Domínguez B [4] used VIKOR for development of renewable sustainable energy plans, Martin-Utrillas, Juan-Garcia, Canto-Perello and Curiel-Esparza [6] integrated the VIKOR, fuzzy Delphi and AHP for selection of best infrastructure related to sustainable economy, Ren, Manzardo, Mazzi, Zuliani and Scipioni [8] combined the VIKOR and AHP for assessment of life cycle sustainability, Yazdani-Chamzini, Fouladgar, Zavadskas and Moini [7] used the VIKOR, SAW, ARAS, TOPSIS and MOORA for selection of the best renewable energy sources, Civic and Vucijak [9] utilized VIKOR for insulation options for warmth of buildings to increase energy efficiency, Kim and Chung [10] evaluated the vulnerability of the water supply to variability and climate change. In total, 13 past papers used the VIKOR technique in the fields of sustainability and renewable energy, which presented in Table 10.…”
Section: Sustainability and Renewable Energy Fieldsmentioning
confidence: 99%
“…The amount of investment required for the implementation of the enhancement is considered as an inexcusable criterion (Martin-Utrillas et al, 2015c). Can be divided in three subcategories.…”
Section: First Questionnaire and Decision Hierarchy Structurementioning
confidence: 99%
“…Modern society cannot live without utilities, and their sustainable development should be incorporated as a key factor in urban underground space (UUS) planning (Cano-Hurtado and Canto-Perello, 1999). This need is part of European Union policy in order to pursue the objective of sustainable development to ensure a high level of environmental protection (Steurera and Bergerb, 2011;Martin-Utrillas et al, 2015a). Bobylev (2009) suggested that UUS should be addressed in urban planning to improve the use of city resources.…”
Section: Introductionmentioning
confidence: 99%